Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/celc.201800324
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bisulfite‐Free Detection of 5‐Methylcytosine by Using Electrochemical Measurements Aided by a Monoclonal Antibody

Abstract: The detection of the epigenetic DNA marker 5‐methylcytosine (5mC) has been the focus of intense research. Here, we report a new detection method, using electrochemical impedance spectroscopy, scanning electrochemical microscopy, and voltammetric measurements on gold electrodes. The direct, label‐free detection of 5mC at different positions within dsDNA is achieved with the aid of a monoclonal anti‐5mC antibody, providing a new tool to monitor nucleic acid modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This method is based on treating DNA with sodium bisulfite which leads to the deamination of cytosine residues and converts them to uracils that are detected as thymines after polymerase chain reaction (PCR), while 5‐mC residues remain intact and are detected as cytosines. This method can detect 5‐mC with single‐nucleotide resolution in a genome‐wide approach but cannot distinguish between 5‐mC and its oxidized derivatives (5‐hmC, 5‐fC and 5‐caC) . Bisulfite‐modified DNA can be analysed by specific PCR methods, such as methylation‐specific PCR (MSP) or coupled to next generation sequencing.…”
Section: Conventional Methods To Detect Epigenetic Modifications Of Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is based on treating DNA with sodium bisulfite which leads to the deamination of cytosine residues and converts them to uracils that are detected as thymines after polymerase chain reaction (PCR), while 5‐mC residues remain intact and are detected as cytosines. This method can detect 5‐mC with single‐nucleotide resolution in a genome‐wide approach but cannot distinguish between 5‐mC and its oxidized derivatives (5‐hmC, 5‐fC and 5‐caC) . Bisulfite‐modified DNA can be analysed by specific PCR methods, such as methylation‐specific PCR (MSP) or coupled to next generation sequencing.…”
Section: Conventional Methods To Detect Epigenetic Modifications Of Nmentioning
confidence: 99%
“…So far, the latest advances in electrochemical biosensing of methylated bases in nucleic acids have demonstrated that the determination can be made in assay times of only 45 min at global or gene‐specific level in spiked samples (urine, saliva and serum), in cancer cells (gDNA, mRNA and RNA t extracts) and in real samples from cancer patients including plasma and serum (gDNA and circulating DNA) and fresh and paraffin‐embedded tissues (gDNA). Methylation events have been determined at the specific level for the following genes of great relevance in cancer diagnosis, classification, prognosis and therapeutic actions: hTERT , FAM134B , p16INK4 , MGMT , RASSF1 A and SF1 .…”
Section: Electrochemical (Bio)sensing Of Nucleic Acid Epigeneticsmentioning
confidence: 99%